2012
DOI: 10.1002/cjoc.201200470
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Decomposition Mechanism of 1,1‐Diamino‐2,2‐dinitroethylene on Al(111) Surface by Periodic DFT Calculations

Abstract: The adsorption of 1,1-diamino-2,2-dinitroethylene (FOX-7) molecule on the Al(111) surface was investigated by the generalized gradient approximation (GGA) of density functional theory (DFT). The calculations employ a supercell (4×4×2) slab model and three-dimensional periodic boundary conditions. The strong attractive forces between oxygen and aluminum atoms induce the N-O bond breaking of the FOX-7. Subsequently, the dissociated oxygen atoms and radical fragment of FOX-7 oxidize the Al surface. The largest ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…They found that the adsorption of the RDX molecules on the Al surface leads to a configurational transformation from “AAE” to “AAA”, and the obtained Al-RDX infrared and vibration spectra are in good agreement with experimental observations. Ju et al. conducted a series of DFT calculations on the adsorption, decomposition, and reaction of common EMs on the Al(111) surface and obtained the related adsorption energy and activation energy. Zhou et al investigated the adsorption and initial decomposition path of a TNT molecule on the Al(111) surface and obtained the adsorption energy as well as the maximum charge transfer between nanofragments and Al.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the adsorption of the RDX molecules on the Al surface leads to a configurational transformation from “AAE” to “AAA”, and the obtained Al-RDX infrared and vibration spectra are in good agreement with experimental observations. Ju et al. conducted a series of DFT calculations on the adsorption, decomposition, and reaction of common EMs on the Al(111) surface and obtained the related adsorption energy and activation energy. Zhou et al investigated the adsorption and initial decomposition path of a TNT molecule on the Al(111) surface and obtained the adsorption energy as well as the maximum charge transfer between nanofragments and Al.…”
Section: Introductionmentioning
confidence: 99%
“…Some aluminized FOX-7 compositions were reported [30,31]. Also some molecular orbital calculations were reported on aluminized FOX-7 [32][33][34][35].…”
Section: Fox-7mentioning
confidence: 99%
“…Some aluminized FOX-7 compositions were reported [30,31]. Also some molecular orbital calculations were reported on aluminized FOX-7 [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%